1998
DOI: 10.1161/01.str.29.2.359
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Harboring an Unruptured Intracranial Aneurysm

Abstract: Background and Purpose-The purpose of the present study was to calculate the prevalence and relative risk of unruptured incidental intracranial aneurysms (IAs) among families with IA case(s) compared with the general population in one geographically defined area in East Finland and to identify the risk group that could benefit most from screening for IAs. We compared these results with our earlier study results of familial IA (FIA) cases, with two or more known IA cases in the same family. Methods-The study gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
0
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(94 citation statements)
references
References 42 publications
2
87
0
5
Order By: Relevance
“…[3][4][5] Furthermore, several studies suggested an increased occurrence of IA and SAH in first-and second-degree relatives of SAH, with the incidence rate of 6-10%. [6][7][8][9] Several Mendelian disorders, such as autosomal-dominant polycystic kidney disease and Ehlers-Danlos syndrome type IV are associated with an increased risk of IA formation. 10,11 All these evidence fortified the roles of genetic factors in the pathogenesis of IA.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Furthermore, several studies suggested an increased occurrence of IA and SAH in first-and second-degree relatives of SAH, with the incidence rate of 6-10%. [6][7][8][9] Several Mendelian disorders, such as autosomal-dominant polycystic kidney disease and Ehlers-Danlos syndrome type IV are associated with an increased risk of IA formation. 10,11 All these evidence fortified the roles of genetic factors in the pathogenesis of IA.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The risk of ruptured IAs in first-degree relatives of patients with aneurysmal SAH is Ϸ4 times higher than that in the general population. 2 Genetic and environmental factors play important roles in the pathogenesis of IA, and recent progress in molecular genetics enables the genetic determinants to be approached directly.…”
mentioning
confidence: 99%
“…23) Autopsy studies have reported an overall prevalence between 0.1% and 9.9% (mean frequency 5%). 24,27,32,33,41) Angiographic studies report a prevalence between 0.2% and 15%. 24,27,32,41) In Japan, using MR angiography as part of thè`b rain screening program,'' unruptured-asymptomatic intracranial aneurysms are found in more than 2% of the patients.…”
Section: Resultsmentioning
confidence: 99%